2010
DOI: 10.1080/03122417.2010.11689379
|View full text |Cite
|
Sign up to set email alerts
|

A Minimum Age For Early Depictions Of Southeast Asian Praus in the Rock Art of Arnhem Land, Northern Territory

Abstract: In 2008, we began two related research projects that focus on recent Australian rock art, made after the arrival of Asians and Europeans, in part of northwest Arnhem Land's Wellington Range. This area has extensive and diverse rock art, including many examples of paintings that reflect contact between local Aboriginal people and visitors to their shores. At some sites figures made of beeswax are found superimposed under and over paintings, thus providing a means of obtaining minimum and maximum ages for pigmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
2

Relationship

4
4

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 12 publications
1
90
0
Order By: Relevance
“…Crittenden, 2011;Gardner, 1993), some Mesolithic rock paintings in Spain feature honey gathering (Dams and Dams, 1977) and Aboriginal Australians actually made rock art with beeswax obtained from honey gathering (e.g. see Taçon et al, 2004;Taçon, May et al, 2010). In the Billasurgam caves, Petraglia et al (2009b: 130-131) dated a ceramic-bearing layer in Chapter House North to 4527-4414 cal BP (95.4% CI, using IntCal09), argued to be associated with the onset of the Neolithic.…”
Section: Significance and Discussionmentioning
confidence: 99%
“…Crittenden, 2011;Gardner, 1993), some Mesolithic rock paintings in Spain feature honey gathering (Dams and Dams, 1977) and Aboriginal Australians actually made rock art with beeswax obtained from honey gathering (e.g. see Taçon et al, 2004;Taçon, May et al, 2010). In the Billasurgam caves, Petraglia et al (2009b: 130-131) dated a ceramic-bearing layer in Chapter House North to 4527-4414 cal BP (95.4% CI, using IntCal09), argued to be associated with the onset of the Neolithic.…”
Section: Significance and Discussionmentioning
confidence: 99%
“…More recently, and with particular reference to western Arnhem Land, Taçon and others have highlighted the incorporation of outside influences (Contact art) -European but also including Macassan from Island Southeast Asia -into much recent Aboriginal rock art (e.g. May et al 2010;Taçon et al 2010). …”
Section: Modelling the Chronology Of Western Arnhem Land's Rock Artmentioning
confidence: 99%
“…May et al 2010;Taçon 1992a). Despite decades of archaeological research within this region, the only rock art images to have been dated directly prior to this monograph are 151 mid to late Holocene beeswax images mainly dating to the past 600 years (Gunn and Whear 2008;Gunn et al 2012;Nelson 2000;Nelson et al 1995;Taçon et al 2004Taçon et al , 2010) -with a total of 111 other pictograms superimposed over or subimposed under these (Gunn 2016: Chapter 4;Gunn et al 2012:59-60;Taçon et al 2010:2-4) -and a small excavated broken rock with part of a black linear painting or drawing from an original image of indeterminate form dated to c. 27,000 years ago from Nawarla Gabarnmang Square E (David et al 2013a;see David et al 2014 for the latest calibrations of the originally reported radiocarbon dates). Watchman (1987) also obtained AMS radiocarbon dates on mineral salts in rock crusts to elucidate the ages of associated paintings from four sites in western Arnhem Land.…”
Section: Western Arnhem Land's Rock Art: the Dating Dilemmamentioning
confidence: 99%
“…For several centuries prior to the European colonisation of Australia, Macassan sailors came annually to the northern coast of Arnhem Land to collect and process trepang (MacKnight 1972(MacKnight , 1986Mitchell 1994;Mulvaney 1975;Taçon et al 2010;Wesley et al 2016). The extent of direct contact that inland groups such as the Jawoyn would have had with coastal mariners some 150 km to the northwest, if any, is unknown.…”
Section: The Initial Munanga Contact Period In Jawoyn Landsmentioning
confidence: 99%
“…Chaloupka 1993:190-206;Edwards 1979:32;May et al 2010May et al , 2013Mountford 1956:162, 179;Wesley 2013). Many of these contact motifs depict Macassan and 19th-to early 20th-century European ships (Chaloupka 1993:190-205;Taçon et al 2010); some are of newly acquired artefacts, such as rifles, knives and Macassan kris, and horses (May et al 2013;Wesley 2013); others depict events from the 1880 gold rush in Pine Creek to the west of the plateau (Chinese miners; e.g. Edwards 1979); still others show themes relating to the Second World War (aeroplanes, Darwin wharf; Chaloupka 1993).…”
Section: Introductionmentioning
confidence: 99%